Experiences of violence in older lesbian and gay people: a sociological approach in Costa Rica 2021-2022 - Araya Flores, Jorge Tomás (2024)
Introduction: In Costa Rica, there is a gap in political, legal, institutional, and various social programs concerning older lesbian and gay individuals, which exposes this population to various forms of violence due to their age and sexual orientation. Objective: The study aimed to investigate the elements that shape the forms of violence experienced by older lesbian and gay individuals in Costa Rica during the period 2021-2022. Method: Life stories were employed as a method, along with in-depth interview techniques and non-participant observation applied to older lesbian and gay individuals in Costa Rica. Results: The research results expose experiences of intersecting forms of violence, a typology of violence manifested in the invisibility of older lesbian and gay individuals, discrimination in healthcare centers and workplaces, exclusion and repression of their sexual identity in healthcare centers and long-stay facilities, and, finally, a heightened violence experienced by older lesbian women. Conclusions: By identifying these forms of violence through their life stories, the characteristics and relationships between the elements that shape these forms of violence become visible. Invisibility conceals a complex network of exclusion, discrimination, and violence that involves both their sexual orientation and older age, which magnifies a reality of violence in their daily lives.